Interceptive and orthodontic treatment provided by pediatric dentists in Jordan - Rajab, Lamis; Murad, Enas; Abu-Ghazaleh, Suha (Jordan Medical Journal, 2022)
Objectives: The purposes of this study were to document the interceptive and orthodontic treatment currently provided by pediatric dentists in Jordan, to determine the type(s) of treatment and appliances provided, and to ascertain variables that would inﬂuence practitioners’ treatment patterns. Methods: A cross-sectional survey carried out among pediatric dentists. A structured questionnaire was used, distributed directly by hand to individual pediatric dentist at place of practice, and collected after one week. Descriptive analysis and Chi-square test were used. The level of significance was set as 0.05. Results: The majority of pediatric dentists (89%) provided orthodontic treatment. Pediatric dentists have unlikely expectations concerning the benefits of orthodontic treatment. The most frequently provided treatments were for space maintenance (99%), and oral habits conditions (94%). The most utilized appliances were space maintaining appliances (99%), habit breaker appliances (83%), upper removable orthodontic appliances (with finger or Z spring and anterior expansion screw) (66%), and palatal expansion appliances (53%). Variables that would significantly affect the type of treatment and appliances used were place of practice, annual hours spent in continuing education in orthodontics, confidence level in providing treatment, and nearest orthodontist’s location. Conclusions: Most of the pediatric dentists provide orthodontic treatment with high expectations concerning the benefits of providing it. This study documents the interceptive and orthodontic treatment currently provided by pediatric dentists in Jordan. It summarizes treatment and appliances provided, and variables that would inﬂuence practitioners’ treatment patterns.